(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
An experiment was carried out with farmer group in Ebonyi State, Southeastern Nigeria, on two hectares of well prepared land with the aid of a tractor and with the aim to find out the impact of positive selection on Dioscorea rotundata seed tuber yam production from two sources in Ebonyi Southeastern Nigeria. The area was divided into Farm A and Farm B. The yam variety used was white yam variety Hembakwasa cultivar. Each hectare of land was planted 10000 seed yam tubers obtained from two different sources. Farm A from the markets vendors and Farm B from farmer saved own seed tuber yam in the farming community. The seed yam tubers were planted on the crest of the ridges at depth of 10cm and at spacing of 1.0m within plant stands and between rows of plants 1.0m. Ten thousand seed tuber yams weighing between 150 and 250g each were planted per stand. All agronomic practices such as weeding, staking, N.P.K fertilizer application 15: 15:15 was carried out on both farms. The farmers were assisted by research scientist to carry out positive selection in farm B only every two weeks while in Farm A the observed crops with symptoms were to be tagged, recorded and allowed to continue growing. The following data were carried out every two weeks: number of plants affected by pathogens, number of yam mixture, number of vigorous and none vigorous yam plants, number of yam plants at harvest, number of yam tuber, number of ware tubers and number of seed yam tubers. Data obtained were analyzed using percentages. Results obtained indicated that sources of seed tuber procurement contributed to lower incidence of pathogen infested plants, more number of vigorous plants, and high number of tubers in Farm B with positive selection compared with Farm A where positive selection was not practiced. High significant number of the yam plants were healthy with yield of very high number of tubers and less varietal mixtures as a result of using healthy pathogen free seed tuber yams from farmers saved own seed at planting coupled with the use of positive selection. If farmers should follow this technique and practice positive selection continuously for several seasons they would progressively have less sick plants in their field.